Protective Effects of Quercetin in Zebrafish Model of Alzheimer’s Disease - Katare, Dr. Deepshikha Pande (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Alzheimer’s disease (AD) is a neurodegenerative disease which is characterized by deposition of amyloid beta plaques and neurofibrillary tangles. The plaques formation affects the synaptic transmission and increases neuroinflammation in brain. Quercetin is the most potent flavonoid which protects brain tissue from neuroinflammation. Zebrafish is a reliable model for the study of neurological disorders. Materials and Methods: Wild adult zebrafishes were used for induction of AD and were done by administrating aluminum chloride intraperitoneally. Behavioral and biochemical estimations were done. Target identification and gene enrichment studies were also performed on probable quercetin receptors. Molecular docking of quercetin in comparison to AD marketed drugs was executed. Results and Discussion: The results showed protective effects of quercetin on AD model. Behavioral and biochemical tests confirm the reduction in oxidative stress and increased cognition. Computational analysis of stereoisomers of quercetin and its different binding positions and modes helps in better understanding of this flavonoid as a drug. Conclusions: Quercetin has protective effects on brain, and this is mediated by its regulating different protein receptors simultaneously.